Postsurgical stability of oropharyngeal airway changes following counter-clockwise maxillo-mandibular advancement surgery - Goncalves, JR; Buschang, P. H.; Goncalves, D. G.; Wolford, L. M. (Elsevier B.V., 2006)
Purpose: This study evaluated oropharyngeal airway changes and stability following surgical counter-clockwise rotation and advancement of the maxillo-mandibular complex.Methods and Patients: Fifty-six adults (48 females, 8 males), between 15 and 51 years of age, were treated with Le Fort I osteotomies and bilateral mandibular ramus sagittal split osteotomies to advance the maxillo-mandibular complex with a counter-clockwise rotation. The average postsurgical follow-up was 34 months. Each patient's lateral cephalograms were traced, digitized twice, and averaged to estimate Surgical changes (T2-T1) and Postsurgical changes (T3-T2).Results: During surgery, the occlusal plane angle decreased significantly (8.6 +/- 5.8 degrees) and the maxillo-mandibular complex advanced and rotated counter-clock-wise. The maxilla moved forward (2.4 +/- 2.7 mm) at ANS and the mandible was advanced 13.1 +/- 5.1 min at menton, 10 +/- 4.4 mm at point B, and 6.9 +/- 3.7 mm at lower incisor edge. Postsurgical hard tissue changes were not statistically significant. While the upper oropharyngeal airway decreased significantly (4.2 +/- 3.4 min) immediately after surgery, the narrowest retropalatal, lowest retropalatal airway, and the narrowest retroglossal airway measurements increased 2.9 +/- 2.7, 3.7 +/- 3.2, and 4.4 +/- 4.4 mm, respectively. Over the average 34 months Postsurgical period, upper retropalatal airway increased 3.9 +/- 3.7 mm, while narrowest retropalatal, lowest retropalatal airway, and narrowest retroglossal airway remained stable. Head posture showed flexure immediately after Surgery (4.8 +/- 5.9 degrees) and extension postsurgically (1.6 +/- 5.6 degrees).Conclusion: Maxillo-mandibular advancement with counter-clockwise rotation produces immediate increases in middle and lower oropharyngeal airway dimensions, which were constrained by changes in head posture but remain stable over the postsurgical period. The upper oropharyngeal airway space increased only on the longest follow-up. (C) 2006 American Association of Oral and Maxillofacial Surgeons.